Under quarantine: immigrants and disease at Israel's gate - Seidelman, Rhona (Rutgers University Press, 2020)
"Under Quarantine is the riveting story of Shaar Ha'aliya, Israel's central immigration camp. Focusing on the conflicts surrounding the camp's medical quarantine, this book brings the history of this place and the remarkable experiences of the immigrants who went through it to live"--